2004
DOI: 10.1038/oby.2004.27
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Childhood Obesity in Japan over the Last 25 Years from the National Nutrition Survey

Abstract: MATSUSHITA, YUMI, NOBUO YOSHIIKE, FUMI KANEDA, KATSUSHI YOSHITA, AND HIDEMI TAKIMOTO. Trends in childhood obesity in Japan over the last 25 years from the National Nutrition Survey. Obes Res. 2004;12:205-214. Objective: To describe the 25-year changes in BMI (measured in kilograms per meters squared) and the prevalence of obesity in Japanese children with special reference to urban-rural differences. Research Methods and Procedures:We used the data sets from the cross-sectional annual nationwide surveys (Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
105
3
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(128 citation statements)
references
References 25 publications
15
105
3
3
Order By: Relevance
“…4 In recent decades, the prevalence of childhood obesity has been increasing in developed countries. 5,6 Some studies have shown that severe obesity in teenagers is associated with an adverse metabolic profile 7,8 and produces endothelial dysfunction and reduced arterial distensibility. 9,10 Furthermore, the early structural changes are a sign of an increased risk of developing atherosclerosis in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…4 In recent decades, the prevalence of childhood obesity has been increasing in developed countries. 5,6 Some studies have shown that severe obesity in teenagers is associated with an adverse metabolic profile 7,8 and produces endothelial dysfunction and reduced arterial distensibility. 9,10 Furthermore, the early structural changes are a sign of an increased risk of developing atherosclerosis in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Obesity is a global health problem with increasing prevalence in many parts of the world. [4][5][6][7] Accurate classification of obesity is important for both the individual and health professionals in risk assessment and weight management. Although body composition or percentage body fat (%BF) can be measured by using several approaches, such as, underwater weighing, body densitometry, bioelectrical impedance analysis, magnetic resonance imaging, isotope dilution method, etc., 8 such methods are complicated and costly, and none has been widely used in individual or epidemiological settings, particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity among Japanese children has increased dramatically and recently has become a serious public health problem (1). Obesity is the most common cause of insulin resistance and hyperinsulinemia (2) and is strongly associated with hypertension, type 2 diabetes mellitus, dyslipidemia and the metabolic syndrome (MS) in childhood.…”
Section: Introductionmentioning
confidence: 99%